2016
DOI: 10.1159/000448813
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on Characteristics and Mortality of Intracerebral Hemorrhage in the Oldest-Old

Abstract: Background: Incidence of acute intracerebral hemorrhage (ICH) increases with age, but there is a lack of information about ICH characteristics in the oldest-old (age ≥85 years). In particular, there is a need for information about hematoma volume, which is included in most clinical scales for prediction of mortality in ICH patients. Many of these scales also assume that, independent of ICH characteristics, the oldest-old have a higher mortality than younger elderly patients (age 65-74 years). However, supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…Gender ( 40 ) and age ( 41 ) are also associated with HE, as men and older subjects (age ≥85 years) are more likely to present HE than women and younger subjects ( 40 , 41 ).…”
Section: Clinical Predictorsmentioning
confidence: 99%
“…Gender ( 40 ) and age ( 41 ) are also associated with HE, as men and older subjects (age ≥85 years) are more likely to present HE than women and younger subjects ( 40 , 41 ).…”
Section: Clinical Predictorsmentioning
confidence: 99%
“…Within this sample, we failed to show that age differences significantly affected outcomes by race. Older age has been associated with ICH etiology [12] and lobar location [12,13], increased hematoma volume and intraventricular hemorrhage [13], as well as poor outcome [24]. However, it has also been shown that advanced age and cerebral atrophy may offer some protection against in-hospital mortality after ICH [25], perhaps due to a greater room for hematoma expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the influence of age, which carries a significant association with ICH etiology [12,13], further compounds these considerations regarding ICH risk factors and outcomes. For example, while recent studies indicated poorer outcomes for White patients after ICH, these disparities were specific for younger adults and from a national perspective [14].…”
Section: Introductionmentioning
confidence: 99%
“…Four patients were also excluded due to pure intraventricular hemorrhage. Finally, 444 patients (156 women [35%]; median age, 69 [IQR 59-79] years; NIHSS score, 9 [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]; median time from symptom onset to admission, 2.60 [1.01-12.0] hours) were enrolled in the present study (see online suppl. Fig.…”
Section: Resultsmentioning
confidence: 99%